Given the following systems of linear equations,
6x + 20y = -62 (Equation 1)
3x - 9y = -12 (Equation 2)
Step 1 : Solve 6x+20y=−62 for x:
6x + 20y + (−20y) = −62 + (−20y) (Add -20y to both sides)
6x = −20y −62
6x/6 = (−20y −62)/6 (Divide both sides by 6)
x = (-10y/3) + (-31/3)
Substitute to Equation 2:
3x−9y=−12
3[(-10y/3) + (-31/3)] - 9y = -12
−19y−31=−12 (Simplify both sides of the equation)
−19y−31+31=−12+31 (Add 31 to both sides)
−19y=19
-19y/-19 = 19/-19 (Divide both sides by -19)
y= −1
Step 2: Substitute −1 for y in x =(-10y/3) + (-31/3)
x =(-10(-1)/3) + (-31/3)
x = -7
Answer:
x=−7 and y=−1